The Influence of Organizational Culture on Internal Communication and Team Performance in Multinational Companies - Muhammad Ras Muis; Ihdina Gustina; Dedy Lazuardi; Putri Wahyuni; Muammar Rinaldi (Outline Publisher, 2025)
This study explores the influence of organizational culture on internal communication and team performance in multinational companies. The research adopts a mixed-methods approach, combining qualitative interviews with managers and employees and a quantitative survey to examine the relationships between organizational culture, communication, and team performance. The findings reveal that a strong organizational culture positively affects internal communication effectiveness, with clear and consistent communication channels enhancing collaboration and alignment among team members. Additionally, the study highlights the significant role of trust, leadership, and cultural integration in fostering effective communication and high team performance. Multinational companies with a unified organizational culture demonstrated higher levels of teamwork, cooperation, and overall performance, while fragmented cultures led to communication breakdowns and reduced team effectiveness. The results emphasize the importance of cultural cohesion, inclusivity, and adaptability in creating a conducive work environment for global teams. This research provides valuable insights for managers in multinational organizations, suggesting that cultivating a strong, trust-based, and inclusive organizational culture can improve communication, enhance collaboration, and drive team success across diverse cultural contexts.